Exploring, Mapping, and Data Management Integration of Habitable Environments in Astrobiology - Chan, Marjorie A.; Bowen, Brenda B.; Corsetti, Frank A.; Farrand, William H.; Law, Emily S.; Newsom, Horton E.; Perl, Scott M.; Spear, John R.; Thompson, David R. (Frontiers in Microbiology, 2019)
New approaches to blending geoscience, planetary science, microbiology-geobiology/ecology, geoinformatics and cyberinfrastructure technology disciplines in a holistic effort can be transformative to astrobiology explorations. Over the last two decades, overwhelming orbital evidence has confirmed the abundance of authigenic (in situ, formed in place) minerals on Mars. On Earth, environments where authigenic minerals form provide a substrate for the preservation of microbial life. Similarly, extraterrestrial life is likely to be preserved where crustal minerals can record and preserve the biochemical mechanisms (i.e., biosignatures). The search for astrobiological evidence on Mars has focused on identifying past or present habitable environments-- places that could support some semblance of life. Thus, authigenic minerals represent a promising habitable environment where extraterrestrial life could be recorded and potentially preserved over geologic time scales. Astrobiology research necessarily takes place over vastly different scales; from molecules to viruses and microbes to those of satellites and solar system exploration, but the differing scales of analyses are rarely connected quantitatively. The mismatch between the scales of these observations— from the macro- satellite mineralogical observations to the micro- microbial observations— limits the applicability of our astrobiological understanding as we search for records of life beyond Earth. Each-scale observation requires knowledge of the geologic context and the environmental parameters important for assessing habitability. Exploration efforts to search for extraterrestrial life should attempt to quantify both the geospatial context and the temporal/spatial relationships between microbial abundance and diversity within authigenic minerals at multiple scales, while assimilating resolutions from satellite observations to field measurements to microscopic analyses. Statistical measures, computer vision, and the geospatial synergy of Geographic Information Systems (GIS), can allow analyses of objective data-driven methods to locate, map, and predict where the “sweet spots” of habitable environments occur at multiple scales. This approach of science information architecture or an “Astrobiology Information System” can provide the necessary maps to guide researchers to discoveries via testing, visualizing, documenting, and collaborating on significant data relationships that will advance explorations for evidence of life in our solar system and beyond.